Sensing via Intestinal Sweet Taste Pathways - Young, Richard L. (Frontiers in Neuroscience, 2011)
The detection of nutrients in the gastrointestinal tract is of fundamental significance to the control of motility, glycaemia and energy intake, and yet we barely know the most fundamental aspects of this process. This is in stark contrast to the mechanisms underlying the detection of lingual taste, which have been increasingly well characterised in recent years, and which provide an excellent starting point for characterising nutrient detection in the intestine. This review focuses on the form and function of sweet taste transduction mechanisms identified in the intestinal tract; it does not focus on sensors for fatty acids or proteins. It examines the intestinal cell types equipped with sweet taste transduction molecules in animals and humans, their location, and potential signals that transduce the presence of nutrients to neural pathways involved in reflex control of gastrointestinal motility.